A3α‐peptidoglycan extracted from Bifidobacterium sp. could enhance immunological ability of Apostichopus japonicus. (7th October 2014) - Zhang, C.Y.; Chen, G.F.; Wang, Y.Y.; Xu, Z.; Wang, Y.G.; Song, X.L.
Abstract To assess the effects of A3α‐peptidoglycan (A3α‐PG) extracted from Bifidobacterium sp. on the immune response and disease resistance of sea cucumber, different concentrations (0, 0.5, 5 and 50 mg mL−1) of A3α‐PG suspensions were used to perform hypodermic injection on Apostichopus japonicus, followed by a Vibrio splendidus challenge. Total coelomocyte count (TCC), phagocytosis activity and activities of four immunological enzymes in both cell‐free coelomic fluid (extra‐cellular, EC) and coelomocyte lysate supernatant (intracellular, IC), including acid phosphatase (ACP), alkaline phosphatase (ALP), superoxide dismutase (SOD) and peroxidase (POD), were measured at 2, 6, 14 and 24 h post injection (hpi). The TCC was not significantly affected (P > 0.05) by A3α‐PG, ranging from 1.84 × 106 to 3.53 × 106 cells mL−1. The coelomocyte phagocytosis activity was significantly activated (P < 0.05) in all the A3α‐PG treatments, whereas no significant difference was observed between them except 24 hpi (P > 0.05). The EC‐ACP activity in the 5.0 mg mL−1 treatment increased significantly (P < 0.05) at all sampling times, while the IC‐ACP activity in the 50 mg mL−1 treatment increased significantly (P < 0.05) at 2 hpi. Also, the 5.0 mg mL−1 treatment had significant (P < 0.05) increase in the EC‐ALP activity within 14 hpi and the EC‐POD activity at 2 hpi, respectively, while significantly (P < 0.05) enhanced IC‐ALP and IC‐POD activities were observed in the 50 mg mL−1 treatment within 6 hpi and at 2 hpi, respectively. Only the 5.0 mg mL−1 treatment showed significant (P < 0.05) increase in the EC‐SOD activity at 2 hpi and IC‐SOD activity within 14 hpi, respectively. The challenge test showed that the animals treated with 50 mg mL−1 of A3α‐PG had notably lower cumulative mortality after 14 days following V. splendidus exposure. All together, these results suggest that A3α‐PG could positively enhance immune response that effectively promotes the health status of A. japonicus against V. splendidus infection.